A Critical Evaluation of Advanced Multi-Carrier Modulation Scheme for 15-Level Inverter via PSO-PID Controller. (2016) - Hemachandu, P.; Reddy, V.C. Veera
Abstract: Particle swarm optimizing mechanism has been shown as a fruitful problem solving tool in a global optimization areas. So far, most of this algorithm is working properly by utilizing an imperative learning pattern, which process the all swarms utilizes in the unique strategy. The grid integrated system is interpretation of stand-by module to co-generation scheme; it combines a PV/FC arrangement with a high recognized power conditioning. Utilization of high voltage gain power conditioning units which plays a crucial role in a grid connected system with a single module. The module ranges from 100 V to 300 V getting from 10 V to 40 V input, then incorporated to micro-grid system via proposed asymmetrical inverter with PSO-PID controller. The formal tuning of the PID controller generates an unreasonable peak over-shoot; more error content will be counteracting by meta-heuristics approaches by a swarm optimizer. This controller forecasts the optimal modulation index & switching angles for attaining enhanced output voltages, in-limit THD resolution & averts the sudden variations. In this behaviour, the proposed scheme provides perfect sinusoidal grid voltages which are in-phase with the current, good harmonic limitation values by using PSO-PID controller. A simulink model is implemented to validate the appearance of proposed 15-level asymmetrical inverter topology with PSO-PID controller by advanced modulation schemes using Matlab/Simulink platform & results are conferred.